Physical and combustion properties of agricultural residue bio-char bio-composite briquettes as sustainable domestic energy sources - Lubwama, Michael; Yiga, Vianney Andrew; Muhairwe, Frank; Kihedu, Joseph (Renewable energy, 2020)
Domestic energy sources in sub-Saharan Africa are still mainly comprised of firewood and charcoal. One of the main challenges affecting the uptake of carbonized briquettes is their inefficiency in transferring heat. In this study bio-composite briquettes were developed from rice husks, coffee husks and groundnut shells, in varying proportions. The briquettes were developed under low pressure (≤ 7 MPa) after carbonization and application of starch binder. Thermal properties of the developed bio-composite briquettes were determined by using a bomb calorimeter and thermogravimetric analysis to determine calorific values and physical properties, respectively. Drop strength tests and particle density determinations were performed to study the mechanical strength and integrity of the developed briquettes. The water-boiling test was used to determine time taken to boil 1 liter of water. Fourier’s Law of heat conduction was used to investigate heat transfer rates across the briquettes for conditions of binder/binder-less bonding conditions. Calorific values for the developed briquettes ranged between 16.6 MJ/kg and 22 MJ/kg. Results for drop strength for the developed composite briquettes were all above 86 %, indicating satisfactory characteristics. Bio-composite briquettes developed using coffee and rice husks bio-chars took less time to boil water compared to all the other bio-composite briquette combinations. Particle densities ranged between 430 kg/m3 and 580 kg/m3. Heat transfer was enhanced when no binder was present and coffee and rice husks were sequentially placed in the briquette composition. This study showed the advantages of producing bio-char bio-composite briquettes over single constituent briquettes. Bio-composite carbonized briquettes produced from rice husks, coffee husks and groundnut shells are a suitable and sustainable alternative to firewood and charcoal use in sub-Saharan Africa.
Keywords: Bio-composite briquettes; Burning rates; Carbonization; hermogravimetric analysis